FREQUENCY OF RECURRENT LARYNGEAL NERVE INJURY AFTER SURGERY FOR PATENT DUCTUS ARTERIOSUS - Khan, Kiramat ullah; Iqbal, Muhammad; Khan, Junaid Ahmad; Junaid, Muhammad; Shah, Shahid Ali; Wazir, Ibrar Mohibullah (Khyber Journal of Medical Sciences, 2022)
OBJECTIVE: To determine the frequency of recurrent laryngeal nerve injury after surgery for patent ductus arteriosus. METHODOLOGY: This Descriptive study was conducted in the Cardiovascular Department, of a tertiary care hospital in Khyber Pakhtunkhwa over a period of six months. Infants with patent ductus arteriosus and failed medical treatment were selected from outpatient setting and admitted in surgical ward of the hospital for further workup. After written informed consent, all the infants were put on next OT list for surgical closure of PDA which were performed by single experience cardiothoracic surgeon using standard left posterolateral thoracotomy approach. At the time of exudation anesthetist looked for any Vocal cord paralysis. Post operatively all infants were kept in ward for the next one day and symptoms on the basis of mother of the child complaining of stridor (on history and physical examination),coughing and choking while feeding and hoarseness of voice were assessed 24 hrs after the surgery. RESULTS: The frequencies and percentages for of recurrent laryngeal nerve injury were 12 (11.42%) after PDA surgery. CONCLUSIONS: This study documented recurrent laryngeal nerve injury after patent ductus arteriosus ligations. The percentage suggests that a higher proficiency in patent ductus arteriosus ligations needs to be ensured in pediatric surgery training programs. KEYWORDS: Laryngeal Nerve Injury, Patent ductus arteriosus, Congenital Heart Diseases (CHD)